Alignment of supramolecular J-aggregates based on uracil-functionalized BODIPY dye for polarized photoluminescence. Issue 80 (10th September 2020) - Zhang, Yongjie; Liu, Ping; Pan, Hongfei; Dai, Haitao; Ren, Xiang-Kui; Chen, Zhijian
Abstract : The H-bonding directed supramolecular J-aggregates of a uracil-functionalized BODIPY dye are uniaxially aligned through the rubbing method to generate highly polarized photoluminescence. Abstract : A BODIPY dye functionalized with uracil-ethynyl groups at the 2, 6-positions supramolecularly polymerized into J-aggregates directed by intermolecular H-bonds and featured intense absorption and resonant fluorescence. The alignment of J-aggregated chromophores in a thin film was achieved by a rubbing method and polarized photoluminescence with a dichroic ratio up to 14.3 was obtained.